2008
DOI: 10.1007/s00467-007-0698-5
|View full text |Cite
|
Sign up to set email alerts
|

Masked severe stenosing ureteritis: a rare complication of Henoch-Schönlein purpura

Abstract: Henoch-Schönlein purpura (HSP)-associated stenosing ureteritis represents a rare complication of the disease, typically presenting with severe manifestations. This article reports on a 3.5-year-old boy with HSP and severe nephritis who developed a unilateral stenosing ureteritis with atypical manifestations, resulting in a nonfunctional kidney and consequent nephrectomy. The urinary tract ultrasound was normal in the first week of illness, and the diagnosis was made during follow-up 8 months after onset. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…The long-term prognosis of Henoch-Schönlein syndrome is nearly totally attributable to kidney disease [1]. The present review complements the results of a preliminary review of the literature published 5 years ago [26]. It confirms that ureteral or vesical involvement, whose occurrence has never been analyzed quantitatively, is very rare, but, if present, is associated with substantial morbidity.…”
Section: Discussionsupporting
confidence: 80%
“…The long-term prognosis of Henoch-Schönlein syndrome is nearly totally attributable to kidney disease [1]. The present review complements the results of a preliminary review of the literature published 5 years ago [26]. It confirms that ureteral or vesical involvement, whose occurrence has never been analyzed quantitatively, is very rare, but, if present, is associated with substantial morbidity.…”
Section: Discussionsupporting
confidence: 80%
“…Obstruction of the ureter and ureteritis may occur as a result of HSP [17]. Therefore, it is important to perform ultrasounds routinely throughout the course of HSP to assess for possible ureteric complications [18]. Several cases have been reported in which patients undergoing treatment for prostate or bladder cancer develop HSP.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Corbett et al [17] reported a 7-year-old African American boy with HSP who experienced bilateral sclerosing ureteritis, developing 4 weeks after the onset of HSP. Siomou et al [18] reported a 3-year-old boy diagnosed with unilateral stenosing ureteritis 8 weeks after the onset of HSP. In some cases, as in the case described by Siomou et al [18], ureteritis may be accompanied by nephritis, which may conceal underlying symptoms of ureteritis.…”
Section: Urological Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple organ involvement may be present from the outset of the disease or, alternatively, an evolving pattern may develop, with different organs becoming involved at different time points over the course of several days to several weeks. One complication worth emphasizing for pediatric nephrologists is the rare but well-recognized complication of ureteric obstruction [13]. …”
Section: Henoch–schönlein Purpuramentioning
confidence: 99%